Enfrentamento da violência e Atenção Primária à Saúde: a visão dos usuários do SUS/BH - Manayá de Souza Vieira (2020)
Violence is a worldwide issue, which affects from whole countries to small communities, causing serious consequences for both individuals and the public sector. Given its impact, this subject should be an important aspect for public awareness and research, changing perspectives and allowing “New actions” to be taken, resulting in new public health polices and prevention actions against violence. Views and actions against violence varies for different groups in society. Hence, taking into account how actions against violence are managed in Brazil, and more specific in the city of Belo Horizonte, this study aims to understand violence by the lens of the public cared for the primary care of the Unified Health System. In this dissertation, an exploratory, descriptive study with a quantitative approach was carried out. The data analyzed on the study was based on a field research entitled Program of Health Promotion and Violence Prevention in Primary Health Care, coordinated by the department of Preventive Medicine of the Federal University of Minas Gerais, the research was conducted on to the public cared for the primary care of the Unified Health System in Belo Horizonte in 2017. The field research consists of a semi-structured questionnaire with 310 questions in which some personal, social and family characteristics, as well as situations of violence in the area covered by the primary care unit, were defined as independent variables, and the coping with violence as a dependent variable. The study proposes a new Indicator of the Perception and Copping of violence that helps to understand the issues even after taking into account the theoretical limitations find in the literature. The interviewees were 1,125 people selected from nine different districts of Belo Horizonte. The criteria for the interviewees were: live in the same place for more than 06 months, to be 16 years old or older and to have been seen at the primary care unit at least once before the interview. According to the data analyzed, the interviewees' perception of violence, can be summarized as follows: Women who suffered violence had higher, more heterogeneous perception than men in the same condition, while individuals with income below minimum wage had a higher perception than those with higher earnings. Those belonging to the age group of 55 to 64 years old had a higher perception than other age groups. Individuals with lower degree of education had a lower perception of coping with violence than those with higher education. Most participants believed that violence can be avoided, and recognize the essential role of primary care of the Unified Health System and the public polices in preventing and coping with violence, however, they do not identify the policies of the government that are focused on this issue. This study made it possible to correlate the characteristics of the population and coping with violence with the policies adopted by the city and the impact they have on the sampled population.